2021
DOI: 10.1038/s41598-021-93569-y
|View full text |Cite
|
Sign up to set email alerts
|

Drying and temperature induced conformational changes of nucleic acids and stallion sperm chromatin in trehalose preservation formulations

Abstract: Even though dried sperm is not viable, it can be used for fertilization as long as its chromatin remains intact. In this study, we investigated drying- and temperature-induced conformational changes of nucleic acids and stallion sperm chromatin. Sperm was diluted in preservation formulations with and without sugar/albumin and subjected to convective drying at elevated temperatures on glass substrates. Accumulation of reactive oxygen species was studied during storage at different temperatures, and the sperm ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Lee et al, 2019; Silva et al, 2020). Importantly, in addition to the immediate effect of dehydration, the incidence of DNA damage increases with higher storage temperatures and longer storage duration in air‐dried equine sperm (measured by Fourier transform infrared spectroscopy) (Brogna et al, 2021), and in lyophilized murine sperm (comet assay) (Kamada et al, 2018; Kawase et al, 2005).…”
Section: Damages and Stresses On Biological Structures And Functions ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Lee et al, 2019; Silva et al, 2020). Importantly, in addition to the immediate effect of dehydration, the incidence of DNA damage increases with higher storage temperatures and longer storage duration in air‐dried equine sperm (measured by Fourier transform infrared spectroscopy) (Brogna et al, 2021), and in lyophilized murine sperm (comet assay) (Kamada et al, 2018; Kawase et al, 2005).…”
Section: Damages and Stresses On Biological Structures And Functions ...mentioning
confidence: 99%
“…We have already mentioned trehalose as one of the main xeroprotectants that mitigates most of the damages, by stabilizing cellular membranes, proteins, and DNA during dehydration (Brogna et al, 2021; Crowe, 2012; Wolkers & Oldenhof, 2021; M. Zhang et al, 2016). Trehalose substitutes water molecules during dehydration to form hydrogen bonds with a lipid membrane, proteins, or nucleic acids, which maintains three‐dimensional (3D)/ordered conformations and structures (Golovina et al, 2010; Jain & Roy, 2009).…”
Section: Mitigations Of Detrimental Effects On Biological Structures ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Trehalose is the most commonly used disaccharides due to its high glass transition temperature (T g ; the temperature at which molecular property changes from liquid to amorphous glass). The beneficial effect of trehalose in protecting spermatozoa against desiccation stress has been demonstrated in spermatozoa from the mouse [11][12][13], cat [14], stallion [15], macaque [16], and human [17]. For example, McGinnis et al reported a significant higher developmental potential of mouse sperm when desiccated in medium with trehalose than in medium without, resulting in a four-to tenfold increase in blastocyst formation [12].…”
Section: Introductionmentioning
confidence: 99%